Comparative Genomics of Staphylococcus Reveals Determinants of Speciation and Diversification of Antimicrobial Defense - Coates-Brown, Rosanna; Moran, Josephine C.; Pongchaikul, Pisut; Darby, Alistair C.; Horsburgh, Malcolm J. (Frontiers in Microbiology, 2018)
The bacterial genus Staphylococcus comprises diverse species with most being described as colonizers of human and animal skin. A relational analysis of features that discriminate its species and contribute to niche adaptation and survival remains to be fully described. In this study, an interspecies, whole-genome comparative analysis of 21 Staphylococcus species was performed based on their orthologues. Three well-defined multi-species groups were identified: group A (including aureus/epidermidis); group B (including saprophyticus/xylosus) and group C (including pseudintermedius/delphini). The machine learning algorithm Random Forest was applied to prioritise orthologues that drive formation of the Staphylococcus species groups A-C. Orthologues driving staphylococcal intrageneric diversity comprised regulatory, metabolic and antimicrobial resistance proteins. Notably, the BraSR (NsaRS) two-component system (TCS) and its associated BraDE transporters that regulate antimicrobial resistance showed limited distribution in the genus and their presence was most closely associated with a subset of Staphylococcus species dominated by those that colonise human skin. Divergence of BraSR and GraSR antimicrobial peptide survival TCS and their associated transporters was observed across the staphylococci, likely reflecting niche specific evolution of these TCS/transporters and their specificities for AMPs. Experimental evolution, with selection for resistance to the lantibiotic nisin, revealed multiple routes to resistance and differences in the selection outcomes of the BraSR-positive species S. hominis and S. aureus. Selection supported a role for GraSR in nisin survival responses of the BraSR-negative species S. saprophyticus. Our study reveals diversification of antimicrobial-sensing TCS across the staphylococci and hints at differential relationships between GraSR and BraSR in those species positive for both TCS.